Enhancing inclusivity and diversity in trials that use routinely collected data: a scoping review - Munnery, Kim; Shepherd, Victoria; Lugg-Widger, Fiona; Dibigbo, Amaka; Lloyd, Christopher; Trubey, Rob; Ahmed, Nageen; Hood, Kerenza; Cannings-John, Rebecca; Murray, Macey L; Mafham, Marion; Robling, Mike (International Journal of Population Data Science, 2025)
Objectives The aim of the scoping review was to identify the existing literature on public and professional’s perspectives about inclusivity and diversity in trials that use routinely collected data. The review will inform the development of training for researchers to promote best practice for inclusive trial design. Methods The scoping review followed the 6-stage Arksey and O'Malley methodology framework, involving a systematic search of relevant databases and selection of publications based on predefined criteria. Those included were collated, summarised and reported using a thematic approach. The review included international publications to ensure a global perspective. The findings have been discussed in consultation with the HDR UK-funded Transforming Data for Trials’ public advisory group and key messages have been embedded into a training module to ensure its relevance and applicability. This module specifically focusses on equity insights for those that work on trials that use health systems data (HSD). Results We will present the results of the scoping review, including how the use of HSD can enhance inclusive trial design and areas where it does not. Preliminary results from 47 publications to date indicate a range of views from under-served groups toward the use of this data in trials from both public and professional opinion. The review has also identified data-enabled strategies and challenges related to inclusivity and diversity in trials. A training module is in development to begin to address these challenges, providing practical guidance and resources to enhance trialist’s best practice knowledge around inclusive trial design using HSD. The public voice is represented in the interpretation of the scoping review findings and content of the training, including key quotes and discussions from workshops. Conclusion This work explores ways to make trials more inclusive and diverse when using HSD and will contribute to building capacity in the field of real-world data research. The training will offer valuable insights into different research partners perspectives, guiding future inclusive trials and training initiatives.